The nexus between environmental concern and future childbearing aspirations among university students in Bangladesh - Bijoya Saha; Shah Md Atiqul Haq (PLoS ONE, 2025)
This study investigates the relationship between environmental concerns and future childbearing aspirations among university students in Bangladesh. It included 380 final-year and master’s students from various academic disciplines at Shahjalal University of Science and Technology (SUST), Bangladesh, who completed a structured questionnaire. The binary logistic regression model and Poisson regression model were employed to examine the effects of these variables (environmental concern, gender, religion, academic performance, university courses related to the environment or climate change, field of study, and perceived vulnerability to extreme weather events or climate change in their home region) on intentions to have children in the future. The findings demonstrate that environmental concerns significantly impact university students’ intentions to have children. Additionally, students who are concerned about environmental issues are more likely to desire children in the future and plan to limit their family size due to these concerns. Students’ future parenting plans are strongly influenced by their perceptions of environmental challenges. According to this study, female students are less likely to intend to have children if environmental conditions worsen. The findings suggest that several factors, including gender, disciplinary background, and environmental degradation, may influence future fertility intentions and, consequently, affect population dynamics. Such factors may also play a crucial role in shaping future population policies aimed at addressing the effects of climate change and achieving environmental sustainability.